Trends in Woody Biomass Utilization in Turkish Forestry - Mehmet Eker (Croatian Journal of Forest Engineering, 2014)
This study aims to provide information to all stakeholders and present an analysis of the trends in the biomass utilization for bioenergy generation to the forestry sector. The analysis focuses on forest resources, production and consumption of wood products, actual situation and trends in the bioenergy sector and forest services. One of the major challenges faced by the Turkish forestry sector is to meet the increasing demand for wood raw material in the wood products industry taking into consideration the trends in the bioenergy sector to promote the renewable energy sources. Therefore, another objective of the study is to determine the available biomass and to reveal its estimated theoretical potential as energy wood. Two projections were performed by using a scenario-based analysis (pessimistic and optimistic projections for bioenergy) of woody biomass supply based on the existing databases, outlook studies, financial balance sheets and progress in renewable energy generation. Special attention was paid to the impact of the forest industry factors that determine the woody biomass potential and to the gaps and uncertainties in the current situation. Consequently, it was found that the bioenergy production based on woody biomass has not been developed yet, although there was 1,494.5 million m of growing stock in nearly 21.7 million ha of forestland, in Turkey. However, the total amount of industrial roundwood production increased by approximately 2.12 fold while the fiber chip board production increased by 29 times in the Turkish forestry sector in the last three decades. Surprisingly, the traditional fuelwood production decreased by 69%. The findings reveal that fiber chip board industry is a competitor to the bioenergy sector and it seems to become an obstacle to the modern utilization of woody biomass for energy in near future. As the wood products favored by the forest industry sector, it can be assumed that logging residues will become a primary source of bioenergy without compromising the supply of the industrial roundwood and fuelwood. The estimated theoretical biomass potential that was only obtained from the logging residues and did not include secondary and tertiary wood residues and waste was estimated to be equivalent to 3.5–5.5 million tons according to the short-scale scenarios.